Characterization of posttranslational modifications in neuron-specific class III beta-tubulin by mass spectrometry. - Alexander, J E (1991)
Class III beta-tubulin, isolated from adult bovine brain, is resolved into at least seven charge variants on isoelectric focusing gels. To identify the posttranslational modifications responsible for this heterogeneity, a mixture of brain tubulins was treated with cyanogen bromide and the C-terminal fragments from the class III beta-tubulin isoforms were then isolated by binding them to the monoclonal antibody TuJ1. Combined use of tandem mass spectrometry and both subtractive and automated Edman degradation chemistry on the isolated peptides indicates that many of the isoforms differ by phosphorylation at Ser-444 plus attachment of one to six glutamic acid molecules to the side chain of the first glutamate residue, Glu-438, in the C-terminal sequence Tyr-Glu-Asp-Asp-Glu-Glu-Glu-Ser-glu-Ala-Gln-Gly-Pro-Lys.